DEVELOPTMENT OF MATHEMATICAL MODEL FOR CARBONATING OF LOW CLOSE CARBON COMPOSITES WITH TERMOCHEMICAL CHANGE OF COMPONENTS - Каrpеnkо Ann; Tsherbakova , Helen; Prokhorova , Anastasia (Scientific Journal "Metallurgy", 2020)
The paper presents a mathematical model of the carbonization process of carbon composite materials. In the process of mathematical modeling, structural and physics-mechanical changes of the components of the composite, such as carbon fibers, pore-forming materials, phenol-formaldehyde resin, were taken into account. In the process of carbonization of carbon composites, under the influence of temperature, physicschemical transformations occur in the volume of the polymer matrix. To calculate the destruction processes, the micromechanics of composites was used taking into account the processes of destruction and changes in the properties of components. During the experiments, the parameters of random thermostructural functions determined by the thermochemical shrinkage of each component of the carbon composite were determined. The carbonization process was implemented in a shielding gas (nitrogen) with a heating rate of 6 ... 8 K / min to a temperature of 1273 K. The shrinkage of the samples was determined periodically every 373 K. The experimental data obtained in this work and the developed mathematical model of the carbonization of the composite material taking into account thermochemical transformations its components make it possible to predict the properties of the resulting material. The change in shrinkage of the low-density carbon composite material is due to thermochemical transformations occurring with the components of the composite material in the process of carbonization. Up to a temperature of 200 0С, changes occur in the materials - blowing agents, with increasing temperature, gaseous substances begin to be released - the result of the transformation of the matrix material - phenol-formaldehyde resin - into a polymer of a mesh structure. Upon reaching a temperature of 800 °C, the shrinkage of the material changes slightly. The strength of the composite material during carbonization sharply changes after 400 0С and reaches its maximum value of 1.1 MPa at a temperature of 1000 0С. The proposed computer program allows one to select and process experimental data, determine the average values and dispersions of micros tresses in the components of carbon composite materials, evaluate damage to components, evaluate the change in elastic properties, thermo chemical shrinkage coefficients, and linear thermal expansion of the composite for arbitrary carbonization temperatures of carbon composite materials depending from the level of the current temperature.